High-technology entrepreneurship - 229485 Oakey, Ray (New York : Routledge, 2012)
Introduction -- The role of the technical entrepreneur -- Clusters, incubators and science parks -- Research and development -- Selling high-technology small-firm products -- Strategy -- Finance -- Conclusions.